Faktor Penyebab Anak Putus Sekolah di Nagari Ladang Panjang Kecamatan Tigo Nagari Kabupaten Pasaman - Ika Laksita Warti; Yurni Suasti; nofrion nofrion (JURUSAN GEOGRAFI FIS UNP, 2019)
This study aims to describe the factors that cause school dropouts in Nagari Ladang Panjang, Tigo Nagari District, Pasaman Regency. This type of research is qualitative. The subjects in this study were children who dropped out of school and their parents. To determine informants using purposive sampling techniques. The results of the study found that the factors causing school dropouts in Ladang Panjang village were: 1) lack of school interest, namely low learning achievement of children, children felt the lessons given seemed difficult and did not understand the lesson with the feeling of being lazy so staying class. 2) family economic factors, low parental income ranging from Rp 400,000 - Rp 1,500,000 with a number of dependents 3 to 5 people. 3) association with friends who are not in school, and the existence of promiscuity that makes children choose to marry rather than going to school. This has caused many children who are less interested in going to school and prefer to drop out of school.